Tax reform and employment in Europe - John P. Hutton; Anna Ruocco (Eberhard Karls Universität Tübingen, Wirtschaftswissenschaftliche Fakultät, 1998)
The purpose of this paper is to investigate to what extent modifications of tax systems between 1985 and 1992 within major parts of the European Union contributed to changes in the labour market. The principal countries under investigation are Germany, Italy, France and the United Kingdom, and the method of investigation is the numerical Simulation of a multi-country general equilibrium model. Changes in VAT rates and in the personal income tax schedule are investigated. We conclude that a non-trivial part of the labour market changes may be due to reactions of the market to changes in these tax rates.
Keywords: 330; Steuerreform; Steuerwirkung; Beschäftigungseffekt; Wirkungsanalyse; Allgemeines Gleichgewicht; Mehr-Länder-Modell; Deutschland; Italien; Frankreich